Comparative Analysis and Systematic Review of Nanocomposite Resins in Restorative Dentistry: Durability and Antimicrobial Properties - Muhammad Saleem Qureshi; Khadija Akhtar; Farah Tasleem; Permanand; Maleeha Khurram; Ayesha Imtiaz; Muhammad Hussain (Pakistan Journal of Medicine and Dentistry)
Background: Nanocomposite resins became promising materials in restorative dentistry due to the application of nanotechnology to improve durability and microbial resistance characteristics. This systematic review aimed to review the mechanical performance and antimicrobial efficacy of nanocomposite resins.